Improving legal accountability for domestic violence - Ostrohliad O. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of the work is to conduct a review of the draft law on amendments to the legislation on administrative responsibility (responsibility for domestic violence and sexual harassment), due to the need to bring it into line with the Istanbul Convention. To determine the current state of passage of the draft law through all the necessary stages, the impact of the conclusions of the specialized committees on the improvement of the text of the future law and in general compliance by the people’s deputies with the requirements of the legislative technique. The basis of this review is the documents officially posted on the parliament’s website regarding the draft law “On Amendments to the Code of Ukraine on Administrative Offenses and Other Laws of Ukraine in Connection with the Ratification of the Council of Europe Convention on the Prevention of Violence Against Women and Domestic Violence and Combating These Phenomena.” Methodology. The methodology includes a comprehensive review and generalization of available scientific and theoretical material and the formulation of relevant conclusions and recommendations. During the research, the following methods of scientific knowledge were used: terminological, systemic-structural, comparative-legal, and the method of analysis (when analyzing and comparing the existing legislative material with the draft law). Results: In the process of research, it was recognized that the issue of the responsibility of people’s deputies for the quality of their legislative work in the field of legal responsibility requires further research and improvement of legal regulation. Originality. In the process of research, it was established that legislative work on legal responsibility, as a prerequisite for proper law enforcement, needs improvement. Matters of taking into account the conclusions of specialized committees, substantiating budget expenditures, compliance with the requirements of the legislative technique by people’s deputies are actually critical, since a poor-quality draft law will lead to problems in law enforcement in the future. Practical significance. The results of the research can be used in law-making activities to develop the necessary changes to the current legislation of Ukraine on administrative responsibility, as well as to continue further theoretical research in this area.